MUTUAL SOLUBILITY ОF CARBIDES WITHIN MULTICOMPONENT DIFFUSIVE COATINGS ОN HARD ALLOYS - A. A. Shmatov; S. V. Poberezhny (Наука и техника)
An optimization of powder mixtures has been performed with respect to wear resistance of  diffusive carbide coatings on hard alloy Т15К6 (79% WC, 15% TiC and 6% Co) for four three-component systems, viz. Cr–Ti–V, Cr–V–Mo, Cr–Ti–Mo and Cr–V–Nb,). The «composition-properties» diagrams have been plotted using the obtained mathematical models. Optimum three-component diffusive saturation of a hard alloy using carbide-forming elements permits to increase its service life by the factor of 2.2–3.1 as compared with one-component saturation. This significant improvement of wear resistance of three-component diffusive carbide coatings is due to formation of heterogeneous microstructure containing complex alloyed carbides of IV-VI-group metals with 2–30% mutually soluble one- or two- saturating elements.